2017
DOI: 10.1093/aob/mcw285
|View full text |Cite
|
Sign up to set email alerts
|

Nectar replenishment maintains the neutral effects of nectar robbing on female reproductive success of Salvia przewalskii (Lamiaceae), a plant pollinated and robbed by bumble bees

Abstract: Nectar robbing did not affect female reproductive success because nectar replenishment ensures that pollinators maintain their visiting activity to nectar-robbed flowers. Nectar replenishment might be a defence mechanism against nectar robbing to enhance reproductive fitness by maintaining attractiveness to pollinators. Further studies are needed to reveal the potential for interference competition among bumble bees foraging as robbers and legitimate visitors, and to investigate variation of nectar robbing in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…Nectar replenishment of the plant is fast and plentiful and, moreover, does not differ between robbed and legitimate flowers (Ye et al, 2017). In the studied area, the plant is exclusively pollinated as well as robbed by bumble bees.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Nectar replenishment of the plant is fast and plentiful and, moreover, does not differ between robbed and legitimate flowers (Ye et al, 2017). In the studied area, the plant is exclusively pollinated as well as robbed by bumble bees.…”
Section: Introductionmentioning
confidence: 81%
“…var. Most flowers last for 2.5 days before they begin to wilt (Ye et al, 2017). It inhabits hillsides, subalpine meadows, forest margins, roadsides, and thickets, with the flowering season usually running from August to September.…”
Section: Study Species and Locationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Annonaceae species are typically dependent on a single guild of pollinators (Saunders, 2012), the pollinators are not reciprocally dependent since they obtain nutrition from many different sources; the circadian traps are therefore likely to have resulted from evolutionary changes in plant phenology rather than changes in beetle circadian rhythms, and are not the result of co-evolution. The timing of anthesis and floral-reward production within each day are likely shaped by the activity peaks of pollinators in order to maximize pollination efficiency (Stebbins, 1970; Armbruster and McCormick, 1990; Herrera, 1990; Jagadish et al, 2002; Kulloli et al, 2011; Prieto-Benítez et al, 2016). Significantly, however, studies of the relationship between the circadian rhythms of pollinators and floral phenology are generally lacking: although previous assessments of pollinator activity have relied on monitoring of floral visits, it has been suggested that in order to study the evolution of floral changes in response to pollinator activity it is more appropriate to assess pollinator activities independently of their interaction with flowers (Armbruster and McCormick, 1990).…”
Section: Introductionmentioning
confidence: 99%